Urinary calprotectin, kidney injury molecule-1, and neutrophil gelatinase-associated lipocalin for the prediction of adverse outcome in pediatric acute kidney injury - Westhoff, Jens; Waldherr, Sina; Tönshoff, Burkhard; Fichtner, Alexander (European journal of pediatrics, 2017)
Early identification of patients with acute kidney injury (AKI) being at high risk for adverse outcome can influence medical treatment. This study compares urinary calprotectin, kidney injury molecule-1 (KIM-1), and neutrophil gelatinase-associated lipocalin (NGAL) for their performance in predicting mortality and need for renal replacement therapy (RRT) in pediatric AKI patients. Urinary biomarker concentrations were assessed prospectively in 141 subjects aged 0-18 years including 55 patients with established AKI according to pediatric Risk, Injury, Failure, Loss, and End-stage kidney disease (pRIFLE) criteria, 27 patients without AKI, and 59 healthy children. Within the AKI group, receiver operating characteristic (ROC) curve analysis revealed moderate to poor performance of calprotectin and KIM-1 in the prediction of 30-day mortality (calprotectin area under the curve (AUC) 0.55; KIM-1 AUC 0.55) and 3-month mortality (calprotectin AUC 0.61; KIM-1 AUC 0.60) and fair performance in the prediction of RRT requirement (calprotectin AUC 0.72; KIM-1 AUC 0.71). Urinary NGAL showed good performance in predicting 30-day (AUC 0.79) and 3-month (AUC 0.81) mortality and moderate performance in predicting RRT (AUC 0.61). Conclusions: Whereas urinary calprotectin and KIM-1 can be useful for the prediction of RRT, urinary NGAL has a good diagnostic performance in predicting mortality in pediatric patients with AKI of heterogeneous etiology. What is known: • There is increasing evidence that urinary biomarkers like neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1) are valuable for the prediction of adverse outcome in adult acute kidney injury (AKI), whereas data on pediatric AKI is scarce. What is new: • Urinary calprotectin and KIM-1 do not predict mortality in our heterogeneous pediatric AKI cohort, but they show moderate performance in the prediction of dialysis. • Urinary NGAL is a good predictor of mortality performing better than pRIFLE stage, eGFR, or creatinine, but it shows moderate performance in the prediction of dialysis.